2019
DOI: 10.1039/c8dt04725a
|View full text |Cite
|
Sign up to set email alerts
|

Acceptorless dehydrogenative construction of CN and CC bonds through catalytic aza-Wittig and Wittig reactions in the presence of an air-stable ruthenium pincer complex

Abstract: Acceptorless dehydrogenative construction of CN and CC bonds catalysed by air-stable ruthenium complexes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 97 publications
0
21
0
Order By: Relevance
“…16 Definitively, these are just a few instances amongst the plethora of organic transformations catalysed by manganese that have been reported in the last lustrum. [17][18][19][20][21][22][23][24][25][26] Encouraged by our interests in the unravelling of the mechanistic aspects in the catalytic chemistry of manganese, [27][28][29][30] the recent work by Milstein et al, 31 reporting for first-time a manganese-catalysed coupling of alcohols and hydrazone to form alkenes, caught our attention. As an alternative to the classical approaches for the synthesis of olefins from carbonyl compounds (such as Wittig, 32 Peterson, 33 or Julia 34 olefinations), Milstein and co-workers offer an unprecedented base-and waste-free procedure for the direct transformation of alcohols into alkenes.…”
Section: Introductionmentioning
confidence: 99%
“…16 Definitively, these are just a few instances amongst the plethora of organic transformations catalysed by manganese that have been reported in the last lustrum. [17][18][19][20][21][22][23][24][25][26] Encouraged by our interests in the unravelling of the mechanistic aspects in the catalytic chemistry of manganese, [27][28][29][30] the recent work by Milstein et al, 31 reporting for first-time a manganese-catalysed coupling of alcohols and hydrazone to form alkenes, caught our attention. As an alternative to the classical approaches for the synthesis of olefins from carbonyl compounds (such as Wittig, 32 Peterson, 33 or Julia 34 olefinations), Milstein and co-workers offer an unprecedented base-and waste-free procedure for the direct transformation of alcohols into alkenes.…”
Section: Introductionmentioning
confidence: 99%
“…We next turned our attention to screen the solvent. As shown in Table 1, we found that the solvent (EtOAc and MeCN) had no significant effect on the reaction (entries 11,12). In addition, lower yield was observed when reaction time was reduced to 0.1 hour due to incomplete conversion (entry 13).…”
Section: Scheme 1 Isomerization Of Alkenesmentioning
confidence: 88%
“…These spectroscopic data match those previously reported. 11 (E)-1-Nitro-4-(pent-1-en-1-yl)benzene (E-1b) Yellow oil; yield: 50.9 mg (89%); E/Z >15:1. These spectroscopic data match those previously reported.…”
Section: (E)-pent-1-en-1-ylbenzene (E-1a)mentioning
confidence: 99%
“…(E)-1-Methyl-3-styrylbenzene (E-1c). 21 E-1c was prepared with 3methylbenzaldehyde (2 mmol, 240 mg, 235 μL) as the substrate according to general procedure B as a white solid (170.7 mg, 44% yield, mp = 50.5−51.3 °C). (E)-1,2-Di-o-tolylethene (E-1d).…”
Section: ■ Conclusionmentioning
confidence: 99%